Interrupted Catalysis: The EF4 (LepA) Effect on Back Translocation - Liu, Hanqing (2010)
EF4, though similar structurally to the translocase EF-G, promotes back translocation of tRNAs on the ribosome, and is important for bacterial growth under certain conditions. Here, using a coordinated set of in vitro kinetic measures, including changes in the puromycin reactivity of peptidyl tRNA and in the fluorescence of labeled tRNAs and mRNA, we elucidate the kinetic mechanism of EF4-catalyzed back translocation and determine the effects of the translocation inhibitors spectinomycin and viomycin on the process. EF4-dependent back translocation proceeds from post-translocation complex (POST) to pre-translocation complex (PRE) via a four-step kinetic scheme, i.e., POST → I(1) → I(2) → I(3) → PRE, that is not the simple reverse of translocation. During back translocation, movements of the tRNA core regions and of mRNA are closely coupled to one another, but are sometimes decoupled from movement of the 3′-end of peptidyl–tRNA. EF4 may be thought of as performing an interrupted catalysis of back translocation, stopping at the formation of I(3) rather than catalyzing the complete process of back translocation culminating in PRE complex formation. The delay in polypeptide elongation resulting from transient accumulation of I(3) is likely to be important for optimizing functional protein biosynthesis.